2001
DOI: 10.1038/sj.bjp.0704325
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptors modulate trigeminovascular nociceptive neurotransmission in the trigeminocervical complex

Abstract: 1 GABA (g-aminobutyric acid) receptors involved in craniovascular nociceptive pathways were characterised by in vivo microiontophoresis of GABA receptor agonists and antagonists onto neurones in the trigeminocervical complex of the cat. 2 Extracellular recordings were made from neurones in the trigeminocervical complex activated by supramaximal electrical stimulation of superior sagittal sinus, which were subsequently stimulated with L-glutamate. 3 Cell ®ring evoked by microiontophoretic application of L-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 69 publications
(71 reference statements)
3
23
0
Order By: Relevance
“…Q-PCR gene expression analysis demonstrated that two of GABA receptor subunits examined (GABRA3 and GABBR2) were significantly down regulated in case subjects in comparison to control subjects. This is consistent with previous research that has suggested that individuals with migraine have a lower level of inhibition in the brain, and that this may be the result of decreased GABA A receptor activation (Storer et al, 2001;Storer et al, 2004;Schiene et al, 1996). As GABRA3 has a chromosomal location of Xq28, a region previously linked to migraine, this strengthens the implication of this genomic location in migraine etiology.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Q-PCR gene expression analysis demonstrated that two of GABA receptor subunits examined (GABRA3 and GABBR2) were significantly down regulated in case subjects in comparison to control subjects. This is consistent with previous research that has suggested that individuals with migraine have a lower level of inhibition in the brain, and that this may be the result of decreased GABA A receptor activation (Storer et al, 2001;Storer et al, 2004;Schiene et al, 1996). As GABRA3 has a chromosomal location of Xq28, a region previously linked to migraine, this strengthens the implication of this genomic location in migraine etiology.…”
Section: Discussionsupporting
confidence: 90%
“…This theory is supported by a study in 2001, demonstrating that after Transcranial Magnetic Stimulation, MA patients were more susceptible to hyperexcibility in the visual cortex than controls, indicating that MA patients may have a lower level of inhibition in the cerebral cortex than control subjects (Mulleners et al, 2001). Other studies have suggested that this lack of inhibition may be due to defective gamma-aminobutyric acid (GABA) circuits (Palmer et al, 2000;Fierro et al, 2003) Decreased GABA A receptor activation and expression has been demonstrated in several studies to result in decreased inhibition within the brain (Storer et al, 2001(Storer et al, , 2004Schiene et al, 1996), suggesting that GABA receptor activation and expression may be decreased in individuals with migraine.…”
Section: Introductionmentioning
confidence: 95%
“…Valproic acid, an inhibitor of γ aminobutyric acid (GABA) aminotransferase, when applied to the rat in the trigeminocervical nociceptive models, reduced the expression of c-fos-positive cells in the TNC [46] after trigeminal stimulation. Electrophysiologic studies, combined with microiontophoresis, also suggested that GABA receptors modulate trigeminovascular nociceptive transmission in the trigeminocervical complex [47].…”
Section: Laboratory Studiesmentioning
confidence: 98%
“…However, it also receives other inputs that participate in head pain control. The parasympathetic system (vagus nerve), together with the TNC and LCN (trigeminocervical [46]; 5-HT 1 receptors for dihydroergotamine; opioids-receptor [47]; GABA-A-receptors [48,49]; trigeminocervical complex-trigeminal nucleus caudalis and lateral cervical nucleus [10,[15][16][17]23,44,45]; hypoglossal afferents [22]; simpato afferents [20,21]. structures), could increase or decrease the pain signals.…”
Section: Autonomic-trigeminocervical Connectionsmentioning
confidence: 99%
“…Recent clinical studies in migraine have indicated the efficacy of potentially GABAergic drugs. Storer et al [16] showed that GABA appears to modulate nociceptive input to the trigeminocervical complex mainly through GABA A receptors. Therefore, GABA A receptors may …”
Section: An Overview Of Migraine Pathophysiologymentioning
confidence: 98%